Consider the graph below:

Which of the following equations does the graph represent?

A) y = ( x - 1 ) ( x + 3 ) ( x + 2 )

B) y = - ( x - 1 ) ( x + 3 ) ( x + 2 )

C) y = ( x + 1 ) ( x - 3 ) ( x - 2)

D) y = - ( x + 1 ) ( x - 3 ) ( x - 2 )

Consider the graph below Which of the following equations does the graph represent A y x 1 x 3 x 2 B y x 1 x 3 x 2 C y x 1 x 3 x 2 D y x 1 x 3 x 2 class=

Respuesta :

It would be C) y = ( x + 1 ) ( x - 3 ) ( x - 2 ) because when you graph the points it falls to the left and rises to the right.

Answer:

Option C

Step-by-step explanation:

Given is a graph of the function and we have to find the equation

The graph has x intercepts as -1,2 and 3

Hence the graph will have these terms as factors

(x+1), (x-2) and (x-3)

So function would be of the form

[tex]y=a(x+1)(x-2)(x-3)[/tex]

To find a:

Use the fact that y intercept is 6

When x=0, y=6

i.e. y =a(1)(6)

a=1

Hence funciton is

[tex]y=(x+1)(x-2)(x-3)[/tex]

Option C is right